Culturally Rooted Leadership and Its Role in Shaping School Climate and Teacher Competence: The Case of Ing Ngarso Sung Tulodo - Muhammad Ihsan Dacholfany; Agus Wibowo; Cipto Handoko; M. Sururi; Muhammad Rijal Fadli; Mohd Mahzan Awang (Prodi Manajemen Pendidikan Islam Pascasarjana Institut Pesantren KH. Abdul Chalim Mojokerto, 2026)
This study investigates the influence of school principals’ leadership, grounded in the Javanese philosophy of Ing Ngarso Sung Tulodo, which, in English, at the front gives an example, and the school climate on the professional competence of elementary school teachers in Indonesia. The Ing Ngarso Sung Tulodo philosophy emphasizes the role of leaders as role models who inspire and guide their subordinates. A positive and supportive school climate is likewise considered essential for fostering teacher development. Adopting a quantitative research design, this study involved 122 elementary school teachers selected through cluster sampling in Lampung Province, Indonesia. Data were collected using a structured questionnaire and analyzed using Structural Equation Modeling (SEM) with SmartPLS 3.0. The results of the study indicate that leadership grounded in Ing Ngarso Sung Tulodo and a conducive school climate have a positive, statistically significant effect on improving teacher competency (p < 0.001). This result differs from most studies of educational leadership at the global level, which still focus on the dominance of Western leadership models and rarely integrate local cultural values as the primary basis for analysis. This study explicitly fills this gap by presenting a leadership model rooted in local wisdom. This study provides a new space for empirical testing of culture-based leadership to improve teacher competency. This area has so far been under-researched in the international literature. Theoretically, this study enriches the study of educational leadership by broadening the perspective of leadership models through the integration of non-Western cultural values. Practically and internationally, this study can provide important implications for policymakers and school administrators, especially in multicultural and developing countries, in designing leadership development programs and school governance that are contextual, globally relevant, and sensitive to local culture.